Evaluate and Rank the Risks in Supply Chain in Work and Initiative of Naghshe Jahan Company - Parsa, Kia; Torfi, Fatemeh (International Review of Management and Marketing, 2017)
The fundamental objective of supply chain management is to integrate various suppliers to satisfy market demand. Supplier evaluation and selection is very important for establishing an effective supply chain. In fact, supplier selection consists of both qualitative and quantitative criteria, so it is considered as a multi-criteria decision-making problem. In this paper, evaluate and rank the risks in supply chain in order to determine and prioritize the critical, which is measured based on determined indexes. we got a list of risks by interviewing experts in this field using failure modes and effect analysis questionnaire the qualitative data are converted to quantitative data and identified risks have been evaluated and ranked by using gray analysis consequently. This study is looking for identifications and descriptions with proper samples of six main kind of confronted risk of supply chain. Hence, the method can be an efficient and effective methodology to be used by decision makers on supply chains. The proposed methodology can also be applied to found the most important known risks, which are proposed, to managers. Keywords: Supply Chain, Risk, Grey Failure Mode and Effect Analysis JEL Classification: R41